Analisis Sistem Pendingin Baterai Li-Ion Berbentuk Silindris Menggunakan Metode Computational Fluid Dynamics (CFD) - Ardhyanti, Novi; Salim, Alfi Tranggono Agus; Apriyanto, R. Akbar Nur (JMPM (Jurnal Material dan Proses Manufaktur), 2023)
The decrease in battery performance, cycle life, and battery safety is caused by the work factor of LiFePo4 (Lithium iron phosphate) battery exceeds the operational temperature of 40OC. The research problem is heat distribution with cooling system variation and fluid effect for LiFePo4 battery. The research objective is to analyze the heat distribution of the battery and the temperature of the LiFePo4 battery below the operational temperature. The research method is quantitative experiment, with Computational Fluid Dynamics (CFD)simulation for LiFePo4 battery cooling system. LiFePo4battery without cooling plate was simulated for maximum battery temperature result. The operational temperature of the battery is lower by 40OCwith additional cooling plates assembled on the battery with variations of water and air fluids that flows in the cooling plates. The results and conclusions of the research are data on the maximum battery temperature increase of 1,2OCand the distribution of heat evenly on the surface of the battery with a variation of the cooling plate flowing with water fluid.